Teacher Difficulty in Conducting Research Class Action at Three Selected High Schools in Muaro Jambi - Sri Ramdayeni Sakunti; M. Rivanda Debi (Journal of Curriculum and Pedagogic Studies (JCPS), 2022)
The aim of this research is to describe teacher problems in conducting classroom action research (CAR). Another purpose of this research is to describe the teachers understanding of classroom action research in some chosen High School in Muaro Jambi. The type of this research is qualitative research and the subject of this research are teachers of the chosen High School in Muaro Jambi. The method used in this research through in-depth interviews. The result showed that the factors causing difficulties in conducting CAR were that the teachers had difficulty in dividing the teaching time with CAR activities, the teachers had difficulty putting in structured descriptions, the teachers had difficulty diagnosing problems that occurred in the classroom, the teachers had difficult to understand the research method, examined theories and bibliography, and teachers have difficulty in carrying out cycles in CAR. The teachers understanding of CAR has been quite well marked by the enthusiasm of the teacher in conducting CAR and the teachers understand that CAR can lift ranks and support the professionalism of the teachers. The effort made by the school to improve CAR by holding CAR training, seminars, group discussion and provide funding for CAR.